2006
DOI: 10.1093/ajcn/84.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma free fatty acids and left ventricular diastolic function in patients with clinically severe obesity

Abstract: Results:The median (25th and 75th percentile) age and BMI were 46 y (36, 53 y) and 51.5 (42.5, 56.5), respectively. The prevalence of diabetes, hypertension, and insulin resistance were 38%, 53%, and 90%, respectively. Plasma free fatty acid (FFA) concentrations were elevated in the cohort. No association was observed between insulin sensitivity or anthropometric measurements and left ventricular contractile function. However, FFA concentration was independently associated with diastolic function (r ҃ Ҁ0.33, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 42 publications
2
26
1
3
Order By: Relevance
“…94 However it is not known whether this relationship is causal or whether elevated fatty acids directly and adversely effect cardiac function in diabetic patients. Elevated plasma fatty acid levels are also modestly correlated with a decreased diastolic function (rϭ0.33) in severely obese patients, 95 but, again, a causal role of fatty acids or cardiac lipid accumulation in diastolic dysfunction has not been demonstrated. Experimental studies in the perfused rat and mouse hearts have also shown that accelerated fatty acid oxidation contributes to the development of diabetic cardiomyopathies by inhibiting glucose oxidation and lowering cardiac mechanical efficiency 77,96 -98 and that pharmacologically inhibiting fatty acid metabolism and increasing glucose metabolism improves contractile function in diabetes.…”
Section: Circulating Fatty Acids and Cardiac Pathology In Obesitymentioning
confidence: 99%
“…94 However it is not known whether this relationship is causal or whether elevated fatty acids directly and adversely effect cardiac function in diabetic patients. Elevated plasma fatty acid levels are also modestly correlated with a decreased diastolic function (rϭ0.33) in severely obese patients, 95 but, again, a causal role of fatty acids or cardiac lipid accumulation in diastolic dysfunction has not been demonstrated. Experimental studies in the perfused rat and mouse hearts have also shown that accelerated fatty acid oxidation contributes to the development of diabetic cardiomyopathies by inhibiting glucose oxidation and lowering cardiac mechanical efficiency 77,96 -98 and that pharmacologically inhibiting fatty acid metabolism and increasing glucose metabolism improves contractile function in diabetes.…”
Section: Circulating Fatty Acids and Cardiac Pathology In Obesitymentioning
confidence: 99%
“…7 In severely obese patients with a body mass index Ͼ50, the serum concentrations of nonesterified fatty acid show a negative association with load-independent diastolic function. 8 In addition to hemodynamic changes, obesity is also associated with increased risk of atrial fibrillation 9 and ventricular ectopic activity. 10 The mechanisms of cardiac remodeling with obesity are complex.…”
Section: Heart Muscle Disease In Human Obesitymentioning
confidence: 99%
“…In addition, LV biopsies from human hearts undergoing LV assist device implantation for heart failure demonstrate that patients with obesity or diabetes and heart failure have more accumulation of lipid within the myocardium than those with heart failure from other causes [60]. Also more indirectly supporting the theory that excessive FAs may contribute to LV dysfunction in obesity are results from a study relating plasma free FAs an LV diastolic dysfunction [61]. Further studies, including longitudinal and interventional studies are still needed in humans to prove that lipotoxicity occurs as it does in animal models.…”
Section: Obesity and Myocardial Metabolismmentioning
confidence: 92%